Prototype expert system (ES) to determine the potential impact and mitigation measures for agricultural development - Nair, Vikneswaran; Daud, Mohamed; Ganapathi, Nathan (Universiti Putra Malaysia, 1999)
Extensive agricultural development produces adverse environmental consequences. Alteration or removal of natural vegetation has been the primary cause of habitat destruction in native plants and species extinction. Any proposed project that will alter or remove native vegetation must consider the environmental impacts. The need for agricultural development in parallel with sustainable vegetation is of paramount important. The interaction of terrestrial vegetation is essential for a balanced ecosystem. Therefore, the application of a computer technology in the form of an expert system (ES) will be able to help in the analysis and management of agricultural development A consistent and reliable system will be able to aid in potential impact assessment and project mitigation abatement measures. A rule-based system can guide the user in ensuring an environmental friendly agricultural development. Knowledge for this system is elicited from the domain experts and existing literature. Application of the system will lead to a greater environmental conscious society.